Cortical Damage Associated With Cognitive and Motor Impairment in Hereditary Spastic Paraplegia: Evidence of a Novel SPAST Mutation - Lin, Jian-zhong; Zheng, Hong-hua; Ma, Qi-lin; Wang, Chen; Fan, Li-ping; Wu, Han-ming; Wang, Dan-ni; Zhang, Jia-xing; Zhan, Yi-hong (Frontiers in Neurology, 2020)
To determine the cortical mechanism that underlies the cognitive impairment and motor disability in hereditary spastic paraplegia (HSP), nine HSP patients from a Chinese family were examined using clinical evaluation, cognitive screening, and genetic testing. Controls were matched healthy subjects. White-matter fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD), and radial diffusivity (RD; tract-based spatial statistics), cortical thickness (FreeSurfer), and subcortical gray matter (FIRST) based on T1-weighted MRI and diffusion tensor imaging were analyzed. A novel mutation in the SPAST gene (NM_014946.3, c.1321+2T>C) was detected. Patients had motor disability and low Montreal Cognitive Assessment (MoCA) scores. Patients showed significantly decreased total gray- and white-matter volumes, corpus callosum volume, cortical thickness, and subcortical gray-matter volume as well as significantly lower FA and AD values and significantly higher MD and RD values in the corpus callosum and corticospinal tract. Cortical thickness, subcortical gray-matter volume, and MoCA score were negatively correlated with disease duration. Cortical thickness in the right inferior frontal cortex was negatively correlated with Spastic Paraplegia Rating Scale score. Cortical thickness and right hippocampus volume were positively correlated with the MoCA score and subscores. In conclusion, brain damage is not restricted to the white matter in SPG4-HSP patients, and widespread gray-matter damage may account for the disease progression, cognitive impairment, and disease severity in SPG4-HSP.